PENGARUH PELATIHAN 3 S (SDKI, SIKI, SLKI) TERHADAP PENGETAHUAN PERAWAT DALAM PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI UPTD PUSKESMAS MANTANG - Agung Rendana; Sri Muharni (NHM PRESS, 2023)
Puskesmas is a health service facility that organizes public health efforts and first-level individual health efforts. Nursing staff need to understand the applicable standards of nursing care so that they can provide standardized, quality and conducive care for patients and their families. To make nursing care, nurses must have a good level of knowledge, especially documentation. This study aims to determine the effect of 3S training (IDHS, SIKI, SLKI) on nurses' knowledge in documenting nursing care at UPTD Puskesmas Mantang. The design of this study was a pre-experiment with the type of one group pretest posttest. All nurses at the Mantang Health Center as research subjects. The sampling technique with a total sampling of 13 people. The instrument used was a knowledge questionnaire containing the theory of IDHS, SLKI, and SIKI. Then analyzed using non-parametric Wilcoxon test. Univariate results before being given 3S training obtained 23.1% high knowledge, 15.4% moderate knowledge, 61.5% low knowledge, and after 3S training obtained 100% high knowledge. Bivariate results show that there is an effect of 3S training (IDHS, SIKI, SLKI) on nurses' knowledge in documenting nursing care with a p-value of 0.001. It was concluded that there was an effect of 3S training (IDHS, SIKI, SLKI) on the knowledge of nurses in documenting nursing care at the UPTD of Puskesmas Mantang. It is hoped that this research will become a policy material in making standards of nursing care based on the IDHS, SLKI and SIKI to improve nursing services and the quality of nursing care, especially documentation in medical records.